A Rare Case of Mesenteric Chylous Cyst in Infant: Case Report and Review of Literature - Salatto, Alessia; Indrio, Flavia; Campanella, Vittoria; Curci, Marina; Maggipinto, Cosetta; Cocomazzi, Raffaella; Canale, Francesco; Nobili, Maria; Bartoli, Fabio (Frontiers in Surgery, 2021)
The occurrence of a mesenteric cyst (MC) is common in adults while in children and in infants is extremely rare. Clinical presentation may range from asymptomatic, a lump or pain in abdomen to intestinal obstruction or haemorrhage. We report on a rare case of Mesenteric Chylous cyst in an infant with signs and symptoms of intestinal obstruction. Discussion of literature is also reported.